2010
DOI: 10.1007/s00436-010-2054-0
|View full text |Cite
|
Sign up to set email alerts
|

A new gonad-infecting species of Philometra (Nematoda: Philometridae) from the red cusk-eel Genypterus chilensis (Osteichthyes: Ophidiidae) off Chile

Abstract: A new nematode species, Philometra genypteri sp. n. (Philometridae), is described from male and female specimens found in the ovary of red cusk-eel, Genypterus chilensis (Guichenot) (Ophidiidae, Ophidiiformes), from the eastern South Pacific Ocean off the coast of northern Chile. Based on light and scanning electron microscopy examination, the new species differs from most other gonad-infecting Philometra spp. in the length of spicules (126-135 μm), a gubernaculum with dorsal lamella-like structures on its dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Specimens of Philometra chilensis were recorded only in ten mature fish females caught in April (see Moravec et al 2011) when the highest proportion of mature females was found (96.4%). Proportion of mature females for February and September was 67.7% and 80.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens of Philometra chilensis were recorded only in ten mature fish females caught in April (see Moravec et al 2011) when the highest proportion of mature females was found (96.4%). Proportion of mature females for February and September was 67.7% and 80.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moravec et al [6] reported a new gonad-infecting species of Philometra genypteri from the red cuskeel Genypterus chilensis off Chile and Philometra sp. in Johnius belengerii having 48% of infection.…”
Section: Discussionmentioning
confidence: 99%
“…High infections by these nematode parasites on both wild and cultured fishes have been recorded in many economically important species of Perciforms [2][3][4]. The large sized females of these nematodes are usually highly pathogenic, causing serious damages to the fish ovaries and affecting fish reproduction, which were recorded by Moravec and Bakenhaster [5], Moravec et al [6], and Moravec and Justine [7]. Parasitic species in the fish ovary is lethargically distributed to our knowledge mainly in the subtropical and tropical regions of the Indo-Pacific and so far it has been reported from the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…At present, 36 gonad-infecting species of Philometra are known to infect marine and brackish-water fishes (Moravec and Manoharan 2013 Moravec et Manoharan, 2013, P. lateolabracis (Yamaguti, 1935, P. madai Quiazon, Yoshinaga et Ogawa, 2008, P. nemipteri Luo, 2001, P. priacanthi Moravec et Justine, 2009, P. saltatrix Ramachandran, 1973, P. sciaenae Yamaguti, 1941, P. scomberomori (Yamaguti, 1935 and P. terapontis Moravec, Gopalakrishnan, Rajkumar, Saravanakumar et Kaliyamoorthy, 2011 (see Quiazon et al 2008a, b;Moravec andJustine 2009, 2011;Moravec et al 2008Moravec et al , 2011aMoravec and Manoharan 2013). Of these, a distinct dorsal protuberance near the distal extremity of the gubernaculum, which occurs in the new species, is also present only in P. gerrei, P. lateolabracis, P. priacanthi and P. terapontis.…”
Section: Discussionmentioning
confidence: 99%